Analysis of meso and micro frames on active aging in Galicia - Castro-Conde, Cristina Ares; de Nieves Gutiérrez de Rubalcava, Arturo (Cuadernos de Gobierno y Administración Pública, 2017)
This piece of research aims to identify discursive barriers to transferring the EU strategy for active aging. It also delivers policy advice on the field. This is an exploratory study conducted in Galicia, a highly aged Spanish region with extended powers on health and social issues. It applies Goffman´s definition of “frame” that refers to ideas that allow people to confer meaning to their experience. It examines the macro level frame (European), the meso one (policy area) and micro frames (actors). New data were created at both meso and micro levels. The research techniques used are interviews with experts and focus groups composed of active older people living in both urban and rural areas.
Keywords: European Union; aging policies; discursive frame; policy transfer.